Systematic Modeling of Municipal Wastewater Activated Sludge Process and Treatment Plant Capacity Analysis Using GPS-X - Mu’azu, Nuhu Dalhat; Alagha, Omar; Anil, Ismail (Sustainability, 2020)
Mathematical modeling has become an indispensable tool for sustainable wastewater management, especially for the simulation of complex biochemical processes involved in the activated sludge process (ASP), which requires a substantial amount of data related to wastewater and sludge characteristics as well as process kinetics and stoichiometry. In this study, a systematic approach for calibration of the activated sludge model one (ASM1) model for a real municipal wastewater ASP was undertaken in GPS-X. The developed model was successfully validated while meeting the assumption of the model’s constant stoichiometry and kinetic coefficients for any plant influent compositions. The influences of vital ASP parameters on the treatment plant performance and capacity analysis for meeting local discharge limits were also investigated. Lower influent chemical oxygen demand in mgO2/L (COD) could inhibit effective nitrification and denitrification, while beyond 250 mgO2/L, there is a tendency for effluent quality to breach the regulatory limit. The plant performance can be satisfactory for handling even higher influent volumes up to 60,000 m3/d and organic loading when Total Suspended Solids/Volatile Suspended Solids (VSS/TSS) and particulate COD (XCOD)/VSS are maintained above 0.7 and 1, respectively. The wasted activated sludge (WAS) has more impact on the effluent quality compared to recycle activated sludge (RAS) with significant performance improvement when the WAS was increased from 3000 to 9000 m3/d. Hydraulic retention time (HRT) > 6 h and solids retention time (SRT) < 7 days resulted in better plant performance with the SRT having greater impact compared with HRT. The plant performance could be sustained for a quite appreciable range of COD/5-day Biochemical Oxygen Demand (BOD5 in mgO2/L) ratio, Mixed Liquor Suspended Solid (MLSS) of up to 6000 mg/L, and when BOD5/total nitrogen (TN) and COD/TN are comparatively at higher values. This work demonstrated a systematic approach for estimation of the wastewater treatment plant (WWTP) ASP parameters and the high modeling capabilities of ASM1 in GPS-X when respirometry tests data are lacking.